Dual functionality of charge extraction and interface passivation by self-assembled monolayers in perovskite solar cells - Azam, Muhammad; Du, Tian; Wan, Zhongquan; Zhao, Heng; Zeng, Huaibiao; Wei, Runmin; Brabec, Christoph; Luo, Junsheng; Jia, Chunyang (Energy and Environmental Science, 2024)
Perovskite solar cells (PSCs) have shown significant advancements in their device performance; however, their poor long-term stability under operational conditions is a major hurdle that hinders their commercialization. Effective bottom interfacial passivation is crucial for enhancing the device performance. Among the many approaches, self-assembled monolayers (SAMs) are particularly notable due to their exceptional ability for both charge extraction and interfacial defect passivation. In this review, we first demonstrate the issues concealed at the bottom interface and the working mechanisms for the phase separation-based fabrication of p-i-n PSCs. Subsequently, a comprehensive comparison is conducted among various SAMs, which passivate defects in the perovskite bottom interface and charge transport layers (CTLs) and modify the substrate surface properties. Furthermore, recent advancements in understanding how variations in the molecular structure of SAMs influence charge transport and their capability for defect passivation are summarized. Finally, a thought-provoking perspective is presented to stimulate the development of SAM molecules with dual functionality in terms of both carrier extraction and defect passivation.
CRIS-Team Scopus Importer:2024-10-18